Implementation of Demonstration Learning Methods in Increasing the Activity of Classroom Students VI SD Negeri 01 Rantau Alai - Angga Nuraufa Zamzami; Rini Apriyani; Aziz Septiatin; Nova Tri Evriani; Darmadi; Hendri Budi Satrio (Jurnal Pengabdian Cendekia, 2025)
This community service program is in the form of education at SD Negeri 01 Rantau Alai, Kilip Pulau Sila Village, Rantau Alai District, Ogan Ilir Regency, South Sumatra. Learning is a special aspect of education that includes the cognitive, affective, and psychomotor domains. This research is more focused on the learning process of Class VI students, totaling 11 people, by using the demonstration learning method in the learning process. This research aims to increase student activity in the classroom, make it easier for students to understand the material being studied, and make learning more effective and efficient. The results of the research obtained by the researcher are that first, students become active during the learning process, second, students become easier to understand the material being studied by the learning objectives, and third, learning becomes more effective and efficient.